Improving Employee Performance through Competence and Interpersonal Communication - Novalien Carolina Lewaherilla; Gerrit Mathias Pentury; Victor Ernest Huwae (Institute of Computer Science (IOCS), 2022)
This study aims to examine and analyze the effect of competence and interpersonal communication on the performance of PKB employees of the Maluku Province BKKBN Representatives. This type of research is a quantitative research, using a questionnaire as a research instrument. The sampling technique used is simple random sampling. The population of this research is the PKB representative of the Maluku Province BKKBN, totaling 100 employees with a total sample of 50 employees. . The results of the study stated that competence and interpersonal communication partially or simultaneously had a positive and significant influence on the performance of PKB employees of the Maluku Province BKKBN Representatives. The variable of competence and interpersonal communication explains the variable of employee performance by 78.2%,This study aims to examine and analyze the effect of competence and interpersonal communication on the performance of PKB employees of the Maluku Province BKKBN Representatives. This type of research is a quantitative research, using a questionnaire as a research instrument. The sampling technique used is simple random sampling. The population of this research is the PKB representative of the Maluku Province BKKBN, totaling 100 employees with a total sample of 50 employees. . The results of the study stated that competence and interpersonal communication partially or simultaneously had a positive and significant influence on the performance of PKB employees of the Maluku Province BKKBN Representatives. The variable of competence and interpersonal communication explains the variable of employee performance by 78.2%,